Effect of Oil Viscosity as a Quenching Medium on Hardness and Corrosion Rate of Mild Steel After Hardfacing - Muhammad Fatihuddin; Reza Febriano Armas; Ferry Budhi Susetyo; Syamsuir; Basori; Muhammad Yunan Hasbi (Fakultas Teknik Universitas Pancasila, 2026)
This study investigates the effect of oil viscosity as a quenching medium on the hardness and corrosion rate of mild steel after hardfacing. The specimens were quenched using oils of different viscosities (SAE 30, SAE 40, and SAE 50) after hardfacing treatment. Microstructural analysis using an Olympus BX51M optical microscope revealed that lower-viscosity oil produced a more dominant martensitic phase, while higher-viscosity oils resulted in greater formation of ferrite and pearlite due to slower cooling rates. The Vickers hardness test showed the highest hardness value of 460.44 VHN for SAE 30, decreasing to 415.18 VHN for SAE 50. Electrochemical testing indicated that the corrosion current density (Icorr) and corrosion rate increased with oil viscosity, from 95.2 µA/cm² and 1.114 mmpy (SAE 30) to 129.1 µA/cm² and 1.511 mmpy (SAE 50). The results demonstrate that lower-viscosity oils enhance martensitic transformation, improve hardness, and reduce corrosion rate, highlighting viscosity control as a key factor in optimizing post-hardfacing heat treatment performance.